ANALISIS KESULITAN BELAJAR SISWA PADA MATERI INVERTEBRATA DI KELAS X SMA SE-KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG TAHUN PEMBELAJARAN 2016/2017 - Jesaya Surbakti; Martina Asiati Napitupulu (Jurnal Pelita Pendidikan, 2017)
This research aims to know the difficulty of student learning on the matter of invertebrates in class X SMAfrom cognitive, learning-based indicator, and the factors causing difficulty learning the students of class X SMAfrom the Sub-district Pancur Batu learning Year 2016/2017. The design of the research that is used is thedescriptive quantitative. The population in the research is that all the students of class X SMA. Samples taken in acluster random sampling Pancur Batu namely SMA Negeri 1 Pancur Batu, SMA Anastasia Pancur Batu, and SMARakyat Pancur Batu with the number of students 171 people's Senior in High School students from the sub-districtPancur Batu. Data collection technique that is used is the test the results of student learning on the matter ofinvertebrates and questionnaires with students who have learning difficulties. The results of the study showedthat the percentage of students learning difficulties On cognitive knowledge level (C1) 25.91% percent with thecategory of difficulty is the level of understanding (C2) 29.86% with the category of medium difficulty,implementation levels (C3) 34.91% with the category of difficulty medium, analysis levels (C4) 49.79% percentwith the category of difficulty is very high, evaluation levels (C5) 60.39% with category of difficulty is very highlevel of creation (C6) 49.19% with a very high level of difficulty category. The factors that influence the difficultyof learning the most dominant is the internal factors namely pscyhiatric of 80.83% and the health of 78.61% withthe cause of the difficulties learning, while external factors namely schools of 78.46% and subjects of 65.47% withthe cause of the difficulties learning.Keywords: difficulties learning, cognitive, and invertebrates